Native Americans and Science: Enhancing Participation of Native Americans in the Science and Technology Workforce through Culturally Responsive Science Education - Cajete, Gregory A. (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2021)
A major issue that directly affects the participation of Native Americans in the science and technology workforce is the lack of preparation in science and math. This lack of preparation has many causes, but one of the most strategically important issues is the lack of culturally relevant curricula that engage Native American students in learning science in personal, social and culturally meaningful ways. This essay explores the needs, issues, research, and development of culturally responsive science education for Native American learners. A curriculum model created by the author at the Institute of American Indian Arts in Santa Fe, New Mexico, from 1974 to 1994 based on Native American cultural orientations is explored as a case study as one example of how to engage Native American students in science learning and become more prepared to participate in science and technology-related professions. As such, it presents a methodology for how trans-systemic work might be approached in building conceptual bridges between Indigenous and Western views of science.